Characterization and properties of Recycled Acrylonitrile Butadiene Rubber (rNBR) filled Epoxidized Natural Rubber (ENR 25) compound
The uses of recycled rubber in rubber compounding become an alternative method to reduce the landfill of rubber waste and gives opportunity to produce new product. In this research, the study on the properties of recycled acrylonitrile butadiene rubber (rNBR) gloves filled epoxidized natural rubber (ENR 25) has been done. The compounding process was conducted by using two roll mills at room temperature and semi-efficient vulcanization (SEV) system was selected in this study. The scorch time (t2), cure time (t90), maximum torque (MH) and minimum torque (ML) were determined by using a Monsanto rheometer. The determination of rubber vulcanizate’s properties includes tensile test, hardness test, resilience test, swelling test, crosslink density, and SEM. Results in first series indicated that the fine size, S1 of rNBR filled ENR 25 compound contributed to the better properties such as cure characteristics, tensile properties, physical properties and morphology compare to coarser size, S2 of rNBR, mainly at 15 phr of rNBR content. However, the coarse size of rNBR particles size exhibited deterioration in all properties due to agglomeration of rNBR during vulcanization process. The optimum properties (having 15 phr of rNBR filled ENR 25) were selected for further study in second series with incorporation of Imperata Cylindrica as natural filler. Result shows a decrement in tensile properties with the increment of Imperata Cylindrica loading. However, cure characteristics, physical properties and morphological properties show better result at 5 phr loading of Imperata Cylindrica powder especially for fine size, C1 powder. At third series, the incorporation of transpolyoctylene rubber(TOR) as compatibilizer into optimum properties in series 2 shows highest tensile properties at 6 phr of TOR and the rubber become softer as the compatibilizer content increased. Other properties such as cure characteristics, physical properties and morphological properties show an improvement with the presence of TOR into rubber compound.